2017
DOI: 10.1016/j.annemergmed.2016.09.032
|View full text |Cite
|
Sign up to set email alerts
|

CHA 2 DS 2 -VASc Scores and Major Bleeding in Patients With Nonvalvular Atrial Fibrillation Who Are Receiving Rivaroxaban

Abstract: Higher CHADS-VASc scores are associated with increased incidence of major bleeding in nonvalvular atrial fibrillation patients receiving rivaroxaban.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…An association between CHA 2 DS 2 -VASc scores and the incidence of major bleeding has been reported in several previous studies [ 19 , 20 ], in which a higher risk of bleeding was noted in patients with higher CHA 2 DS 2 -VASc scores who were also receiving warfarin or rivaroxaban. We also found a similar association in the patients taking dabigatran or apixaban.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…An association between CHA 2 DS 2 -VASc scores and the incidence of major bleeding has been reported in several previous studies [ 19 , 20 ], in which a higher risk of bleeding was noted in patients with higher CHA 2 DS 2 -VASc scores who were also receiving warfarin or rivaroxaban. We also found a similar association in the patients taking dabigatran or apixaban.…”
Section: Discussionsupporting
confidence: 56%
“…Although it has been reported that higher CHA 2 DS 2 -VASc scores are also associated with an increased incidence of major bleeding in patients receiving warfarin or rivaroxaban [ 19 , 20 ], it is not known whether this phenomenon would be observed in patients taking other NOACs such as dabigatran and apixaban. In this study, we investigated this issue using a nationwide medical insurance claiming database in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…However, these risk scores have only moderate predictive accuracy, especially in the elderly 20. Further complicating matters is the fact that an increased bleeding risk is correlated with an increased stroke risk, since strong bleeding risk factors such as increasing age, vascular disease, or prior stroke are the most important risk factors for ischemic stroke 2123…”
Section: Anticoagulation and High Bleeding Riskmentioning
confidence: 99%
“…Overall, there is a consistent, elevated risk of bleeding, particularly GI bleeding, in rivaroxaban patients compared with warfarin, dabigatran and apixaban users. There appears to be an increased risk in the elderly, those with a higher CHA 2 DS 2 -VASc score and those age >75 years [49,50,60,61]. There are currently risk scores for the assessment of bleeding risk, including the often-used HAS-BLED score [62].…”
Section: The Issue Of Gi Bleedingmentioning
confidence: 99%